THE DISTRIBUTION OF BENTHIC FORAMINIFERA IN DAMAR ISLAND AND JUKUNG ISLAND, SERIBU ISLANDS - Natsir, Suhartati M. (Marine Research in Indonesia, 2010)
Seribu Islands are archipelago within Jakarta Bay built upon the pleistocene coral formation of the Sunda Shelf. The islands are characterized by unique and high biodiversity such as coral reefs. Since coral reef degradation would lead to a decrease of human prosperity, the determination of the coral reef quality is of high importance. Foraminifera offers an early warning system for the coral reef condition, as exemplified by the FORAM Index, i.e. Foraminifera in Reef Assessment and Monitoring Index. This study compared the foraminiferal community structure and the FORAM Index of two islands between the Damar Besar and Jukung. Both islands were dominated by symbiont-bearing foraminifera of the genera Amphistegina, Calcarina, Heterostegina, Marginophora, and Operculina. However, the number of benthic foraminifers at Jukung Island was higher than that at Damar Besar Island, having 17 individuals per species on average. Jukung Island was a conducive site to reef growth, as indicated by a FORAM Index (between 6,48 and 6,57), and Damar Besar Island was liable to environmental change.